Limited sex differences in plastic responses suggest evolutionary conservatism of thermal reaction norms: A meta‐analysis in insects. Issue 6 (2nd November 2022) - Teder, Tiit; Taits, Kristiina; Kaasik, Ants; Tammaru, Toomas
Abstract: Temperature has a profound effect on the growth and development of ectothermic animals. However, the extent to which ecologically driven selection pressures can adjust thermal plastic responses in growth schedules is not well understood. Comparing temperature‐induced plastic responses between sexes provides a promising but underexploited approach to evaluating the evolvability of thermal reaction norms: males and females share largely the same genes and immature environments but typically experience different ecological selection pressures. We proceed from the idea that substantial sex differences in plastic responses could be interpreted as resulting from sex‐specific life‐history optimization, whereas similarity among the sexes should rather be seen as evidence of an essential role of physiological constraints. In this study, we performed a meta‐analysis of sex‐specific thermal responses in insect development times, using data on 161 species with comprehensive phylogenetic and ecological coverage. As a reference for judging the magnitude of sex specificity in thermal plasticity, we compared the magnitude of sex differences in plastic responses to temperature with those in response to diet. We show that sex‐specific responses of development times to temperature variation are broadly similar. We also found no strong evidence for sex specificity in thermal responses to depend on the magnitude or direction of sex differences in development time. Sex differences in temperature‐induced plastic responses were systematically less pronounced than sex differences in responses induced by variations in larval diet. Our results point to the existence of substantial constraints on the evolvability of thermal reaction norms in insects as the most likely explanation. If confirmed, the low evolvability of thermal response is an essential aspect to consider in predicting evolutionary responses to climate warming.